Ethnopharmacology of Karo Oil as Traditional Medicine by Karo Ethnic Group in Berastagi (North Sumatra), Indonesia - Aritonang, Anggi Chatie Yunida; Lubis, Muhammad Fauzan; Sujarwo, Wawan (Ethnobotany Research and Applications, 2024)
Background: The Karo ethnic group in Berastagi, North Sumatra, Indonesia, relies on traditional remedies like Karo oil for various health purposes. However, scientific documentation of its medicinal properties is lacking. This study aimed to document its traditional use, medicinal plants, and community-based development efforts. Methods: Semi-structured interviews were conducted with eight knowledgeable Karo informants. Non-probability sampling ensured selection aligned with research objectives and cultural context. Data were analyzed using the Miles and Huberman Model, exploring medicinal plants and calculating quantitative indices. Results: The study identified 39 plant families and 84 medicinal plants used in Karo oil. Common families were Zingiberaceae, Lamiaceae, Arecaceae, Rutaceae, and Apiaceae. The production involves collecting raw materials, separation, grinding, heating, filtering, and packaging. Karo oil treats muscle and joint disorders, skin conditions, indigestion, fever, and aids in postnatal recovery. Native plant species, like Vitis gracilis and Anoectochilus reinwardtii play a crucial role in traditional medicine. Conclusions: The Karo community possesses rich traditional knowledge of medicinal plants specially for oil production. However, modernization and a lack of successors threaten this knowledge. Conservation efforts are crucial for preserving this valuable cultural heritage. Keywords: Community health, Cultural heritage, Local wisdom, Natural remedies, Traditional healing